1996
DOI: 10.1002/(sici)1096-8644(199610)101:2<137::aid-ajpa1>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status and mortality of highland children in Nepal: Impact of sociocultural factors

P. M. J. F. Huijbers,
J. L. M. Hendriks,
W. J. M. Gerver
et al.

Abstract: This study investigates the nutritional status of native children in the highlands of Nepal (1,700-3,000 m) and explores the relationship between child mortality and surviving children's nutritional status. A random sample of 145 households from 11 villages in the Koshi Hill Zone in east Nepal was surveyed, and the nutritional status of the 438 children < 14 years of age living in these households was assessed by means of anthropometry. We found a severe growth retardation in the Nepalese children compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Major differences in food availability and nutrition do not seem to be an issue in this study. High altitude peasants in the Andes [Frisancho and Baker, 1970;Beall et al, 1977] were found to be better nourished than similar groups in the Himalayans [Huijbers et al, 1996]. Likewise, Ballew and Haas [1986], studying lowland and highland populations in Bolivia, concluded that the low birth weight in high altitudes is not caused by undernutrition but to hypoxia.…”
Section: Discussion Confoundersmentioning
confidence: 99%
“…Major differences in food availability and nutrition do not seem to be an issue in this study. High altitude peasants in the Andes [Frisancho and Baker, 1970;Beall et al, 1977] were found to be better nourished than similar groups in the Himalayans [Huijbers et al, 1996]. Likewise, Ballew and Haas [1986], studying lowland and highland populations in Bolivia, concluded that the low birth weight in high altitudes is not caused by undernutrition but to hypoxia.…”
Section: Discussion Confoundersmentioning
confidence: 99%
“…Working from the basic assumption that people would, in general, rather live longer than shorter lives, it is appropriate to interpret variations in longevity among status groups as differences in the collective success of these groups to achieve the goal of long life. Since the reasons for these differences are complex, it is empirically useful to continue compiling evidence for these relationships by combining paleodemographic and archaeological analyses of individual sites from varying temporal, geographic, and sociocultural contexts (Alesan et al, 1999; Cook, 1981; Derevenski, 2000; Grauer, 1989, 1991, 1993; Knüsel et al, 1997; Mays, 1997, 1999; Powell, 1988, 1991; Robb et al, 2001; Rogers and Waldron, 2001; Šlaus, 2000; Stirland, 1997; Whittington, 1992) and by pursuing clinical, anthropological, and epidemiological projects that tackle similar issues (Bogin and MacVean, 1981; Crooks, 1995; Dobney and Goodman, 1991; Huijbers et al, 1996; Schell, 1997).…”
mentioning
confidence: 99%
“…The annual grain deficits, which range from 4.8 months in western Nepal to 2-3 months in eastern Nepal (Panter-Brick and Eggerman, 1997), have a direct impact on the level of nutrition because cereal grains provide 80-90% of the calories and most of the protein in the Nepali diet (Brown et al, 1968;Koppert, 1988;Panter-Brick, 1997). Widespread protein/energy malnutrition is reported for many regions of Nepal, with roughly 50-60% of the children showing evidence of chronic undernutrition (Brink et al, 1976;Huijbers et al, 1996;Martorell et al, 1984;UNICEF, 1992).…”
Section: Land Scarcity and Grain Deficitsmentioning
confidence: 99%